Disinfectants in a Hemodialysis Setting: Antifungal Activity Against Aspergillus and Fusarium Planktonic and Biofilm Cells and the Effect of Commercial Peracetic Acid Residual in Mice - Lopes, Leonardo G.; Csonka, Larissa A.; Castellane, Jessica A. Souza; Oliveira, Alef Winter; Almeida-Júnior, Sílvio de; Furtado, Ricardo Andrade; Tararam, Cibele; Levy, Larissa Ortolan; Crivellenti, Leandro Zuccolotto; Moretti, Maria Luiza; Giannini, Maria José S. Mendes; Pires, Regina H. (Frontiers in Cellular and Infection Microbiology, 2021)
Aspergillus and Fusarium cause a broad spectrum of infections in humans, mainly in immunocompromised patients. Among these, patients undergoing hemodialysis are highly susceptible to infections, requiring a constant and adequate environmental disinfection program. Nevertheless, monitoring the residual disinfectants can contribute to the morbidity and mortality reduction in these patients. Here, we evaluated the susceptibility of Aspergillus spp. (n=19) and Fusarium spp. (n=13) environmental isolates against disinfectants (acetic acid, citric acid, peracetic acid, sodium hypochlorite, and sodium metabisulphite) at different concentrations and time exposures. Also, we investigated the in vivo toxicity of the peracetic acid residual concentration in mice. Fusarium isolates were identified by F. equiseti, F. oxysporum and F. solani while Aspergillus presented clinically relevant species (A. fumigatus, A. niger and A. terreus) and environmental ones. Against planktonic cells, only two disinfectants (acetic acid and sodium hypochlorite) showed a fungicidal effect on Fusarium spp., while only one (sodium hypochlorite) was effective against Aspergillus spp. Both fungi formed robust in vitro biofilms with large amounts of the extracellular matrix, as evidenced by electron micrographs. Exposure of fungal biofilms to disinfectants showed sensitivity to three (acetic, citric, and peracetic acids), although the concentrations and times of exposure varied according to the fungal genus. Mice exposure to the residual dose of peracetic acid during 60 weeks showed anatomopathological, hematological, and biochemical changes. The implementation of news control measures and those that already exist can help reduce infections, the second cause of death and morbidity in these patients, besides providing safety and well-being to them, a priority of any quality health program.